ANALISIS FINANCIAL LEVERAGE, GROWTH, DAN RISIKO BISNIS TERHADAP PROFITABILITAS PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 PADA PERIODE 2013-2017 - Lorraine Analia Aglen; Yunia Panjaitan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
This study aims to examine the effect of financial leverage, growth, and business risk on firm’s profitability. Using 18 companies listed on LQ45 index during 2013 – 2017. The research used a panel data regression analysis method with Fixed Effect Model (FEM) as the estimator model. The findings suggest that financial leverage has a negative effect on firm’s profitability, asset growth has a positive effect on firm’s profitability, and business risk does not affect firm’s profitability.